Effects of Different Drying Methods on Volatile Flavor Compounds in Idesia Polycarpa Maxim Fruit and Oil - Hongrui Ping; Yonghui Ge; Wenxuan Liu; Jinxiang Yang; Zhaoxue Zhong; Jinhua Wang (Molecules)
This study combined gas chromatography–ion mobility spectrometry (GC-IMS) and multivariate statistical analysis to explore the differences in the characteristic aroma of Idesia polycarpa Maxim (I. polycarpa) fruit and oil under different drying methods: natural drying (ND), hot air drying (HAD), microwave drying (MD), and microwave vacuum drying (MVD). The results revealed that 91 volatile compounds were identified in the fruit, and 82 were found in the oil of I. polycarpa. HAD and MD resulted in the most significant loss of volatile aroma in both the fruit and oil. In contrast, MVD demonstrated the best retention of these volatile aromas. Multivariate statistical analysis and odor activity value (OAV) analysis (OAV ≥ 1) were employed to identify 10 volatile aroma compounds considered differentiating factors in the fruit and oil subjected to different drying methods. These compounds, including hexanal, 3-methylbutyric acid, 2-acetylpyridine, guaiacol, valeraldehyde, and butyric acid, significantly contribute to the flavor characteristics of I. polycarpa fruit and oil, evoking notes of nuts, caramel, and sourness. The OAVs of these aroma-differentiating compounds in microwave vacuum-dried fruit and oil were higher compared to those from other drying methods. Therefore, when considering the enhancement of volatile flavor compounds, MVD is more effective than the other drying methods in promoting the formation of flavor compounds in I. polycarpa fruit and oil.